Studi Literatur Review: Analisis Kesulitan Belajar Mahasiswa Pendidikan Matematika - Avita Salsabila; Rusi Ulfa Hasanah; Desmi Fitri Syahdani Br Sitepu; Siti Zia Hadatul Hasanah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article discusses the learning difficulties experienced by mathematics education students. Learning difficulties are a common challenge faced by students in the learning process, but for mathematics education students, these learning difficulties can have more complex implications. This article aims to identify factors that can cause learning difficulties for mathematics education students, as well as finding effective solutions to overcome these problems. This research uses qualitative methods by conducting interviews and observations of mathematics education students who experience learning difficulties. The research results show that factors such as a lack of understanding of mathematical concepts, anxiety about mathematics, and lack of motivation in learning are the main causes of learning difficulties for mathematics education students. To overcome these learning difficulties, this research recommends an approach that focuses on developing understanding of mathematical concepts, reducing anxiety about mathematics through a more interactive and creative approach, and providing appropriate motivation in the learning process. Apart from that, forming study groups and providing individual guidance are also considered effective in helping students overcome their learning difficulties. It is hoped that this article can provide a deeper understanding of the learning difficulties of mathematics education students and provide recommendations that can help improve the quality of mathematics learning for mathematics education students.